Sistem Pendeteksi Gerakan Berbasis Internet of Things (IoT) - Filisia R. Terok; Ferdinan I. Sangkop; Kristofel Santa (Program Studi Teknik Informatika, 2020)
In Indonesia, burglary is a high priority for the police officer. Security is very important aspect in human life. Every human need security in their house. The desire for better security have push technology boundary for more. The author has developed Motion Detection System Based on Internet of Things(IoT) to accommodate safer environment around the house. This project implement a Raspberry Pi Mini PC, camera and PIR sensor as a security System,making it easier for the homeowner to know the situation of their house when